Grain boundary engineering towards high-figure-of-merit Nd-Ce-Fe-B sintered magnets: Synergetic effects of (Nd, Pr)Hx and Cu co-dopants. (1st February 2021) - Jin, Jiaying; Yan, Mi; Chen, Wang; Zhang, Wenying; Zhang, Zhiheng; Zhao, Lizhong; Bai, Guohua; Greneche, Jean-Marc
Abstract: We present a potent pathway, (Nd, Pr)Hx and Cu grain boundary engineering, to tackle the trade-offs between coercivity, remanence and corrosion resistance of Nd-Ce-Fe-B sintered magnets. Concurrent improvements of magnetic and corrosive properties are achieved in 25 wt% Ce-substituted magnet depending on the (Nd, Pr)Hx /Cu ratio. A representative 8:2 ratio yields room-temperature magnetic performance ( H cj = 14.1 kOe, B r = 12.88 kG, ( BH )max = 39.4 MGOe) equivalent to that of N40M commercial-grade Nd-Fe-B, as well as superb thermal stability (coercivity coefficient | β | of 0.55%/K within the 293-413 K interval) and electrochemical resistance. These outstanding properties are closely correlated to the three notable microstructural characteristics, including (1) an increasing fraction of the REFe2 phase with raised Cu content, (2) the occurrence of a new-type Cu-dissolved REFe2 phase with higher Nd/Pr and lower Ce content than conventional 1:2 phase, and (3) a Cu-dissolved RE-rich phase with deficient Fe. Above structural and chemical features are discussed on the basis of experimental studies, which allow for better continuity of non-ferromagnetic grain boundary phase and higher chemical stability of intergranular regions, thus enabling a good compatibility of magnetic and anti-corrosive performance. Our exploration of (Nd, Pr)Hx and Cu synergy may pave a novel way for developing high-figure-of-merit Nd-Ce-Fe-B permanent magnets that rival the commercial Nd-Fe-B counterpart. Graphical abstract: Image, graphical abstract